Hybrid cloud storage aggregator for private use - Shun, Hanley Hanli (2016)
In this report, we document the implementation of the protocol that allows end-users to protect data that are sent to remote servers using two factors – knowledge (passwords) and possession (a time-based one-time password generation for authentication). The implementation does not require any trusted third-party and also supports invoking a new possession factor in the event that the older possession factor is being compromised provided that the legitimate owner still has a copy of the possession factor. The approach protects the outsourced data from the storage servers themselves by encrypting and dispersing the information parts across multiple servers. The basic protocol is also extended to demonstrate how collaboration can be supported even when the stored content is encrypted, and where each collaborator is still restrained from accessing the data through a multi-factor access mechanism. The scope of this project has strictly been implementing the protocol and not in the design of the basic protocol or its extensions.